The travel trend in the age of TikTok: how older Chinese tourists choose their travel destination – an empirical study using the UTAUT2 Model - Wang, Zhikun; Kamarudin, Syafila; Yaakup, Hani Salwah (Redfame Publishing Inc., 2025)
This study explores the influence of the short video platform TikTok on the travel decision-making process of older Chinese tourists, particularly in destination selection. With the widespread popularity of social media and short video content, the older population has gradually become an important segment in the tourism market. Grounded in the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2), this study investigates the extent to which TikTok shapes and facilitates travel decisions among this population. Through a questionnaire survey and structural equation modeling analysis, the results show that TikTok's performance expectancy, effort expectancy, and hedonic motivation significantly affect the travel decisions of older tourists. At the same time, older tourists are influenced by social influence and habit. However, the study also reveals that facilitating convenience has no significant impact on the behavioral intentions of older tourists, indicating that for older tourists accustomed to using technology, facilitating convenience are not decisive factors. This study enriches the application of short video platforms in the travel decision-making of the older, especially the marketing potential of the emerging TikTok platform. The findings provide practical guidance for tourism marketers to better utilize short video platforms to attract older tourists and influence their travel decisions.